The Role of Dividend Policy as a Mediation Variable on Factors Affecting Company Value - Retno Giansari; Agung Guritno (P3M Politeknik Negeri Banjarmasin, 2022)
This study aims to determine the role of dividend policy (DPR) as a mediator of the relationship between Islamic Corporate Governance (ICG), Investment Decisions (PER), and Funding Decisions (DER) on Firm Value (PBV) in companies registered with JII in 2014-2020, which were 48 companies. The method of determining the sample using the purposive sampling method is based on the criteria for the number of samples obtained by as many as 12 companies. The data analysis technique uses a quantitative approach. Data analysis tool using Eviews 10 with regression analysis selected fixed effect model. The results of this study indicate that ICG has a negative and insignificant effect on PBV, PER has a positive and significant effect on PBV, DER has a positive and insignificant effect on PBV, ICG has a negative and insignificant effect on DPR, PER has a positive and significant effect on DPR, DER has a negative and insignificant effect on the DPR, the DPR has a negative and insignificant effect on PBV, and the DPR is unable to mediate the influence of ICG, PER, and DER on PBV. Based on the F test, it is known that the ICG, PER, and DER variables with DPR as the intervening variable are proven to have a positive and significant effect on PBV.